Large deviation for slow-fast McKean–Vlasov stochastic differential equations driven by fractional Brownian motions and Brownian motions - Chenggui Yuan (Stochastics and Dynamics, 2024)
In this paper, we consider slow-fast McKean–Vlasov stochastic differential equations driven by fractional Brownian motions with Hurst parameter [Formula: see text] and Brownian motions. We give a definition of the large deviation principle (LDP) on the product space related to fractional Brownian motion and Brownian motion, which is different from the traditional definition for LDP. Under some proper assumptions on coefficients, LDP is investigated for this type of equations by using the weak convergence method.